Literature Review Implementation And Challenges In Achieving SDGS: Key Findings From Various Studies - Romi Gunawan; Ketut Sukiyono; Mochamad Ridwan; Mustofa Romdhon (UNIVED Press, 2025)
The goal of national development is welfare and sustainable development to all corners of the country. Villages as territorial the smallest own unique phenomenon. Statement about Topic study or what we know about topic? Or why Topic That important. Statement about objective study or about What study this. Statement about How A study has done or How study the made. Statement about what has been found in study or what was found? Statement about conclusion, implications or recommendation from findings study or what does the findings mean the.